PERENCANAAN PENATAAN LANSKAP KAWASAN WISATA DAN PENYUSUNAN ALTERNATIF PROGRAM WISATA DI GRAMA TIRTA JATILUHUR, KABUPATEN PURWAKARTA, PROVINSI JAWA BARAT - Bambang Sulistyantara; Prita Indah Pratiwi (Jurnal Lanskap Indonesia, 2011)
Grama Tirta Jatiluhur (GTJ) is tourism area which is located in the eastern of Ir. H. Djuanda water reservoir. This tourism area is one of potential tourism destination in Purwakarta which has many objects and attractions. The purpose of this research areto identify and analyze natural tourism resources, to analyze land suitability oftourism area, to analyze ecological value of green open space, to analyze characteristics and perceptions of tourists in GTJ, and to decide touring plan based on objects andattractions. This research use qualitative and quantitative descriptive method. The qualitative descriptive method consists of potentials and constrains of biophysical aspects, technical aspects, and social aspects. Whereas the quantitative descriptive method applies Geographic Information System (GIS) proces by: (1) overlaying thematic maps of physical-biophysical aspects, objects and attractions potentialsvariables using software ArcView 3.2; and (2) calculating the value of nature by using extention CITYgreen 5.4. The results of this research are landscape planning for tourism area and formulation of Tourism Programme Alternatives with ecologicallysustainable development. The landscape plan consists of touring plan, spatial, vegetation, circulation, activities, facilities, and tourism programmes